PENGELOLAAN SUNGAI RANGAU BERBASIS KEARIFAN LOKAL DI DESA RANTAU KOPAR KABUPATEN ROKAN HILIR SEBAGAI RANCANGAN MODUL BIOLOGI SMA - Andrico, Totok; ', Yustina; ', Darmadi (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2017)
Abstract: The research has been done to find out the Local Wisdom of Rantau Kopar Community in Rangau River Management from January to April 2017. The research was used to design the module unit in Biology Learning of Environmental Conservation in SMA, in two stages namely Research and Module Design Unit Module. Data collection with in-depth interview method with snowball sampling technique to key informant that is Adat Leader, Community Leader. In addition, field observation and documentation techniques are used. The results showed that Rantau Kopar community has various local wisdom in implementing Rangau river management, among others, (a) planning includes local knowledge, spatial planning, settlement, irrigation and plantation, (b) The community uses it to maintain the sustainability of resources by utilizing the potential of availability Contained in the Rangau River, (c) controls include the use of environmentally friendly fishing gear and prevention efforts with no prohibition, (d) maintenance of the environment by mutual assistance and the ban on disposing garbage to the river. The results of this study can be used as a unit of learning module Biology on the concept of Environmental Conservation.Keywords: Local Wisdom, Snowball Sampling, Rangau River Management, Module Design.